OPTIMALISASI SIMPANG TAK BERSINYAL (STUDI SIMPANG BANJARAN, TEGAL) - Rahmawati, Kurnia; Siskawati, Tiara Rizky; Maulida, Ardita Puspa (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Unsignalized Intersection in Tegal city, especially Banjaran intersection, recently have a traffic congestion potency. The major streets to the economy centre and residential center causes this. The research was conducted at the three arm unsignalized Intersection. The survei was held on the morning peak hour, peak hour at noon, and evening peak hour. The survei held at Banjaran intersection on Friday and Saturday. The analysis used the Indonesia Highway Capacity Manual 1997. The purpose of the analysis is to acknowledge the traffic stream condition that has access to enter the unsignalized intersection. Within the result, it could be acknowledged that the degree saturation is 1,09, the average delay ismore than 25 second/pcu and queue probability is more than 48,38 %. These indicate that intersection condition is bad. Banjaran intersection needs traffic signal because the performance intersection have been poor and the unsignalized intersection can not be accepted any more.